Analysis of economic indicators in resource efficiency management - Rakhmonkulova Nafis Olimjon kyzy (THE INNOVATION ECONOMY, 2026)
This article provides a comprehensive analysis of the economic indicators of resource efficiency management. The problem of efficient use of resources is of great importance in the activities of modern enterprises. The article studies the main economic indicators of resource efficiency, their interdependence and impact on the efficiency of the enterprise. In the results section, statistical data on enterprises of various industries are analyzed, and correlations between the level of resource efficiency and economic efficiency are identified